Investigation into the use of solid nitrogen to create a "thermal battery" for cooling a portable high-temperature superconducting magnet - Hales, P; Jones, H; Milward, S; Harrison, S (2005)
The design of a portable, "stand-alone" cooling system, for use with a high-temperature superconducting (HTS) magnet, is discussed. The HTS magnet is used to propel a magnetohydrodynamically powered model boat (approximately 120cm × 60cm). The aim of this investigation was to establish the suitability of solid nitrogen for use in the stand-alone cooling system, and determine the optimum method for exploiting its cooling power. It was found that obtaining good thermal contact between solid nitrogen and its container is very difficult if the nitrogen is frozen under vacuum, due to the formation of a thermal barrier between the nitrogen and its container. This problem is overcome if the nitrogen is frozen via conduction cooling from cold helium gas (at ∼4.2K); and the design for a near isothermal "thermal battery" based on this principle is presented, This thermal battery has been constructed and integrated into the HTS magnet system onboard the model boat, and the results from the first trials of this system are presented here. © 2004 Elsevier Ltd. All rights reserved.